Delivering large-scale IT projects on time, on budget, and on value - Bloch, Michael; Blumberg, Sven; Laartz, Jürgen (McKinsey on Business Technology, 2012)
Large IT efforts often cost much more than planned; some can put the w hole organization in jeopardy. The companies that defy these odds are the ones that master key dimensions that align IT and business value.